Reacciones en la comunidad digital ante Trump y su discurso (poético) sobre la inmigración y América Latina - Escandell Montiel, Daniel (Diálogos Latinoamericanos, 2018)
This article discusses how Latin America and immigration appear in The beautiful poetry of Donald Trump, a book of poems authored by British comedian Rob Sears using real statements by Trump. It analyses the creation of this book mainly using the theoretical framework of non-creative writings developed by Kenneth Goldsmith and how the idiolect of Donald Trump is re-created through the poems. Afterwards, the article deals with the main topics of the book with a focus on how Latin America and immigration are portrayed in its pages and how the British point of view of the author can have an impact on the relevance of such themes. Finally, it focuses on the readers’ online conversation regarding this book through the book reviews published on Goodreads, the biggest social network for readers in the world and how its political and satirical point of view is perceived by those readers. In conclusion, the article argues how the book successfully shows the appropriation of Trump’s voice to rebuild his political discourse, and discusses the underlying reasons that cause Latin America and immigration to be underrepresented in the book in comparison with Trump’s presidential campaign appearances.